Pemanfaatan Media Interaktif Berbasis Web dalam Meningkatkan Literasi Digital Siswa - Revi Nur Ridwan; Riyadh Ahsanul Arifin; Windriani L. Azzahra (Ma'soem University, 2026)
The rapid development of digital technology has made digital literacy an essential competency for students in the 21st century, yet many learners still lack the ability to critically evaluate online information and practice responsible digital behavior. This situation was also identified among students at MTS Asy-Syifa, where digital devices are frequently used but digital literacy skills remain limited. This community service program aimed to introduce and implement Web-Based Interactive Media (WBIM) as an interactive learning tool to improve students’ digital literacy, particularly in evaluating digital information, understanding digital ethics, and recognizing cybersecurity risks. The program applied a Participatory Action Research (PAR) approach combined with experiential learning, involving needs analysis, development of WBIM modules, teacher training, and interactive workshops where students engaged in scenario-based digital literacy activities. The results indicate that WBIM created a more engaging learning environment that encouraged students to actively analyze digital content, reflect on ethical aspects of online communication, and develop greater awareness of digital security. These findings suggest that integrating interactive web-based learning media into educational activities can effectively support the development of critical, responsible, and digitally literate students.